Evaluasi BukTahlil Kitab Ilmi al-Shorfi Allafahu Abu Razin wa Ummu Razin Bi Ma’ayir at-Ta’lim al-Wathaniyah al-Indonisiyahu Ilmu Sharaf Untuk Pemula Karya Abu Razin Dengan Standar Yang Ditetapkan Oleh Badan Standar Nasional Pendidikan (BSNP) Indonesia - Muhammad Azhar; Hakmi Wahyudi; Masrun Masrun (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2023)
To get a decent and quality textbook, it is necessary to evaluate and analyze the book, where a quality book will help achieve learning objectives. The purpose of this research is to analyze 3rd edition of the book Shorof science for beginners by Abu Razin published by the Bisa Learning Center, whether the textbook meets BSNP standards based on aspects of material, presentation, language and graphics and whether the book is suitable for beginners. The type of research used is qualitative and bibliographic research which aims to analyze more deeply the book Shorof Science for Beginners by Abu Razin. The method used is documentation study and literature study. Based on the research results, the Shorof science textbook for beginners by Abu Razin is a book that meets BSNP standards and meets the quality of teaching materials based on aspects of material, presentation, language and graphics and is very suitable for use for teaching Shorof science for beginners. The weakness of this book is that there is no Glossary and Summary at the end of the discussion chapter.